Humanitarian crisis due to climate and security challenges in the Far North Cameroon: how the international assistance is organised? - Serge Silatsa Nanda; Rahmawati Hussein; Nur Azizah; Abdoulaye Njoya Nchankou (AEGIS : Journal of International Relations, 2021)
Humanitarian needs in Cameroon have been growing steadily over the years due to the multiple crises the country has been going through. This study aims to analyse the international assistance provided to the populations of Far North Cameroon who are facing security and climate challenges. The study was implemented through the study of pertinent documentation (articles, newspapers, books and reports) related to the issue. Our analysis shows that, the humanitarian needs are critical in the Far North of Cameroon. Indeed, about 33% of households are food insecure, including 3% in a situation of severe food insecurity, 6% of children are affected by Global Acute Malnutrition. Following this situation, only 26% of the requirement in was funded for the year 2020, making Cameroon to be ranked as the world’s most neglected displacement crises by the international community. These funds were received from both foreign countries and private donors from all the continents. The international humanitarian assistance is coordinated by OCHA in collaboration with Cameroon governmental partners, implementing and operational partners and United Nations agencies.